Pengaruh Tempat Kerja terhadap Kesehatan Pekerja dan PAK (Penyakit Akibat Kerja) Berdasarkan Hasil Medical Checkup di PT.X - Jordan Syah Gustav; Shinta Ayu Wulandari (Pusat Riset dan Inovasi Nasional, 2025)
Noise exposure in industrial workplaces can lead to hearing disorders categorized as Occupational Diseases (OD). This study aimed to evaluate the distribution of audiometric disorders based on work divisions and noise levels in PT.X. A descriptive quantitative method with a cross-sectional approach was used. Data were collected from the 2023 annual medical checkup of 133 workers with abnormal audiometry results. The highest prevalence of hearing disorders was found in Feed Production (48.87%), followed by Repair Maintenance (21.05%) and Warehouse (11.28%). Approximately 70% of the cases occurred in high-noise areas, while the rest were found in medium and low-noise areas. These findings indicate a strong correlation between workplace noise levels and the risk of hearing loss. The implications highlight the importance of noise control, regular audiometric screening, consistent use of hearing personal protective equipment (PPE), and worker education as key strategies to prevent occupational hearing disorders.